An insight into the sprawling microverse of microRNAs in depression pathophysiology and treatment response. (March 2023) - Roy, Bhaskar; Dwivedi, Yogesh
Abstract: Stress-related neuropathologies are pivotal in developing major depressive disorder (MDD) and are often governed by gene-regulatory changes. Being a stress-responsive gene-regulatory factor, microRNAs (miRNAs) have tremendous biomolecular potential to define an altered gene-regulatory landscape in the MDD brain. MiRNAs' regulatory roles in the MDD brain are closely aligned with changes in plasticity, neurogenesis, and stress-axis functions. MiRNAs act at the epigenetic interface between stress-induced environmental stimuli and cellular pathologies by triggering large-scale gene expression changes in a highly coordinated fashion. The parallel changes in peripheral circulation may provide an excellent opportunity for miRNA to devise more effective treatment strategies and help explore their potential as biomarkers in treatment response. This review discusses the role of miRNAs as epigenetic modifiers in the etiopathogenesis of MDD. Concurrently, key research is highlighted to show the progress in using miRNAs as predictive biomarkers for treatment response. Highlights: ● miRNAs are critical components in post-transcriptional gene regulation. ● Involvement of miRNAs in stress-related disorders have transformed the field of neurobiology of mood disorders. ● miRNAs can serve both as phenotypic determinants and novel therapeutic targets in depression. ● Circulating blood miRNAs can serve as potential biomarkers in MDD diagnosis and therapeutic responses.